Understanding and Developing Proofs with the Aid of Technology - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2008)
This paper continues the work entitled On Proof Techniques and Technology [see paper for reference], which discusses strategies on how technology may be used to explore and understand mathematical ideas, and develop different kinds of proofs.